Effect of different solvent extracts of Benincasa hispida T. on experimental hypochlorhydria in rat - Upanandan Mandal; Debasis De; Kazi Monjur Ali; Anjan Biswas; Debidas Ghosh (Wolters Kluwer Medknow Publications, 2012)
Hypochlorhydria is a common problem in any age of people like other gastric disorders. It has so many etiologies such as sympathetic dominance, antiseretory drug use, excess sugar and refined foods, etc. In the present study, our objective was to search out the effective solvent extract of fruit of Benincasa hispida T. for the management of hypochlorhydria in model male albino rats. Hypochlorhydria was induced in rat as per standard method by oral administration of ranitidine. Different solvent extracts (Hydro-methanol, ethyl acetate, and aqueous) of ripe fruit of B. hispida were prepared following the standard protocol. Various parameters in this concern like free acidity, total acidity, pH, pepsin concentration, chloride and vitamin C levels in gastric juice were measured by standard biochemical and titrimetric methods. It was found that pre-administration followed by co-administration of aqueous extract of B. hispida (ABH) resulted significant correction of ranitidine-induced hypochlorhydria in rat. This aqueous extract-treated group showed increased levels of vitamin C, pepsin, and chloride concentration in gastric juice as well as the antioxidant status significantly (P<0.05) in respect to other extract-treated groups. From the results, it can be concluded that the ABH has most effective anti-hypochlorhydric and antioxidative efficacy than other solvent extracts of said plant fruit.